A Catalogue of Human Rights Violations in Eritrea ecommendations by Charter- and treaty-based human rights monitoring mechanisms pertaining to social, economic and cultural rights and accountability for crimes against humanity in Eritrea (Pretoria University Law Press (PULP), 2018)
At the 62nd session of the African Commission on Human and Peoples' Rights, April/May 2018, Nouakchott, Mauritania, the Centre for Human Rights co-hosted, together with Amnesty International and Eritrean human DefendDefenders, a side event on the human rights situation in Eritrea. The aim was to draw attention to the situation in the country. On this occasion, the Centre focused on the socio-economic rights situation in Africa, and launched a report on socio-economic rights and accountability in Eritrea.